Necrolytic migratory erythema in a patient with neuroendocrine carcinoma - Gronau, Michaela; Jäger, Dirk; Enk, Alexander; Hassel, Jessica C. (Internal medicine, 2013)
Necrolytic migratory erythema is an obligatory paraneoplastic syndrome. Here we describe a patient with a neuroendocrine tumor of probably pancreatic origin. She developed the typical skin lesions under chemotherapy with temozolomide and capecitabine.